Provision of Chicken Manure and Urea Fertilizer on the Chemical Characteristics of Ultisol Soil in Bilah Barat District - Fitra Syawa Harahap; Iman Arman; Nurliana Harahap; Fauzi Ahmad Syawaluddin; Rendi Fitra Yana (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
Ultisol soils are agricultural lands in Indonesia, which are widely distributed, but have a problem, namely the element of N in the soil is relatively low, so it is necessary to do proper cultivation techniques, one of which is through the provision of balanced fertilizers, namely the application of organic fertilizers that aim to improve soil fertility and reduce soil fertility. use of NPK fertilizers. This study aims to determine the effect of giving various kinds of organic fertilizers, namely sometimes chicken and urea fertilizer on the chemical properties of Ultisol from Pangkatan. This research was carried out at the Agrotechnology Practice Field, Faculty of Science and Technology, Labuhanbatu Rantau Prapat University, with an altitude of 25 meters above sea level. The study began in February 2021 to June 2021. This study used a factorial Randomized Block Design (RAK) with 2 treatment factors. namely: Urea fertilizer factor with four levels and Chicken manure factor with three levels. Soil analysis parameters which include , pH H2O by electrometric method, determination of N-total soil by Kjehldal method, C-organic soil using Wakley and Black method. The results showed that the application of chicken manure was able to increase soil N-toatal in the Ultisol Rank soil, at a dose of U1K3 (Urea: 0.25g and Chicken Manure: 75g) while the interaction of urea and chicken manure application increased the N-total soil of Ultisol Rank with dose of U1K3 (Urea: 0.25g and Chicken Manure: 75g).